2022
DOI: 10.1111/wre.12523
|View full text |Cite
|
Sign up to set email alerts
|

Electricity as an effective weed control tool in non‐crop areas

Abstract: While weed management is often thought of as an agricultural issue, weeds are also problematic for homeowners, public space managers and utilities. In these situations, weeds are typically hand‐pulled, mechanically treated or managed via herbicides. Hand pulling and mechanical treatments are labour‐intensive, and all control methods may have unintended off‐target impacts, necessitating new alternatives for weed control. We have developed a method of using electricity to effectively manage unwanted plants. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…When the application was increased to 200 V, mortality was 79% at 300 s and 90% at both 420 and 540 s (Sahin and Yalınkılıç 2017). Similarly, Lehnhoff et al (2022) found that when treating tamarisk ( Tamarix spp. L.) with experimental continuous plant–electrode contact technology at 2 mA for 0, 12 or 24 h, a reduction of 0%, 37%, and 75% in plant biomass can be seen.…”
Section: Theoretical Understanding Of Weed Responses To Electric Weed...mentioning
confidence: 95%
See 3 more Smart Citations
“…When the application was increased to 200 V, mortality was 79% at 300 s and 90% at both 420 and 540 s (Sahin and Yalınkılıç 2017). Similarly, Lehnhoff et al (2022) found that when treating tamarisk ( Tamarix spp. L.) with experimental continuous plant–electrode contact technology at 2 mA for 0, 12 or 24 h, a reduction of 0%, 37%, and 75% in plant biomass can be seen.…”
Section: Theoretical Understanding Of Weed Responses To Electric Weed...mentioning
confidence: 95%
“…However, the development of applicable electric weed control technology must prioritize the user's safety and those nearby during operation. Lehnhoff et al (2022) recently analyzed the suitability of such applications to xeriscaping using an experimental mesh screen over urban groundcover that was consistently exposed to a safe, low-level current of 6 mA for 4 mo (continuous plant–electrode contact). Compared with the untreated control at 64%, this resulted in only 11% coverage of carelessweed ( Amaranthus palmeri S. Watson), silverleaf nightshade ( Solanum elaeagnifolium Cav.…”
Section: Applicability To Australian Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another physical weed management tactic is weed electrocution, a method patented in the late 1800s (Opp and Opp 1952). The technology was investigated in sugar beets ( Beta vulgaris L.) in the 1970s (Diprose et al 1985; Rasmusson et al 1980; Vingneault and Benoît 2001), and there has recently been renewed interest, likely due to the increase in herbicide-resistant weeds (Heap 2023) and the development of new electrical weeding machines (Bloomer et al 2022; Lati et al 2021; Lehnhoff et al 2022). The flow of electricity through a plant generates heat, which causes water molecules inside the plant vasculature to vibrate at a high intensity, resulting in damage to cell walls and destruction of tissues, ultimately leading to plant death (Lati et al 2021; Vingneault and Benoît 2001).…”
Section: Introductionmentioning
confidence: 99%